Game Online: Ancaman ‘Candu Digital’ - Khamam Khosiin (Ridwan Institute, 2022)
The internet as a product of the development of information technology, brings major changes in human life. The internet provides convenience to various aspects of life, ranging from information, education, economy and business, to entertainment. Entertainment provided through internet services also varies, ranging from reading books, video shows, movies and dramas, to online games. Development development is a process to develop a new product or improve an existing product, which can be accounted for. The game that was first created by Steve Russell and his friends was named Spacewar. This game was created using a mainframe computer named MIT PDP-1 in 1961. As for the Playstation (PS), it only appeared in 2000. Until now PS is still often used, but along with technological developments, online games are increasingly in demand and popular in Indonesian society. Online games as a product derived from the internet have brought major changes to the entertainment trend of the current generation. As interactive entertainment, online games are able to attract many internet users to enjoy them as a means of entertainment. Unfortunately, many online game users are complacent to the end of addiction.